2012
DOI: 10.1159/000338472
|View full text |Cite
|
Sign up to set email alerts
|

Speech Performance and Sound Localization Abilities in Neurelec Digisonic® SP Binaural Cochlear Implant Users

Abstract: In this prospective study the outcome of the Digisonic® SP Binaural cochlear implant (CI), a device enabling electric stimulation of both cochleae by a single receiver, was evaluated in 14 postlingually deafened adults after 12 months of use. Speech perception was tested using French disyllabic words in quiet and in speech-shaped noise at +10 dB signal-to-noise ratio. Horizontal sound localization in quiet was tested using pink noise coming from 5 loudspeakers, from –90 to +90° along the azimuth. Speech scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…The presence of the long electrode array under the scalp (in the BINAURAL group) did not result in any specific intra-or postoperative complications, as reported elsewhere [Truy et al, 2002;Verhaert et al, 2012].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The presence of the long electrode array under the scalp (in the BINAURAL group) did not result in any specific intra-or postoperative complications, as reported elsewhere [Truy et al, 2002;Verhaert et al, 2012].…”
Section: Discussionsupporting
confidence: 72%
“…The performances observed in our study were lower, namely 49.9° for the BINAURAL group and 38.2° for the BILATERAL group (in quiet). Verhaert et al [2012] also reported better localization performances in a group of 14 Neurelec Digisonic ® SP Binaural CI users, with an average angular error of 35°. Litovsky et al [2009] noted that stereophonic hearing abilities might emerge in a two-step process beginning with discrimination in noise and converging on more fine-grained localization.…”
Section: Sound Localizationmentioning
confidence: 84%
See 2 more Smart Citations
“…Consequently, bilateral CI users seem to be favored especially in noise when testing speech intelligibility. When the two CI sound processors become better synchronized, one can hope that the gain will be even greater (Verhaert et al 2012). …”
Section: Bimodal Versus Bilateral: Slight But Significant Advantage Omentioning
confidence: 99%